Mapping of adaptation interventions in Senegal - Ndione, Y. C.; Tall, L.; Sall, S.; Ciss, P. N.; Rousseau, E.; Amarnath, Giriraj; Okem, Andrew (International Water Management Institute, 2023)
The CGIAR Initiative on Climate Resilience is geared towards Building Systemic Resilience against Climate Variability and Extremes in developing countries including Guatemala, Kenya, Morocco, the Philippines, Sri Lanka, Senegal, and Zambia. The initiative has four work packages: 1). De-risking agriculture production systems and livelihood from climate change, 2). Building production system resilience recognizing the linkages of climate, agriculture, security, and peace; 3). Developing adaptation instruments to inform policy and investments, and 4). Multiscale governance for transformative adaptation. Work Package 4 (WP4) expects to set up a bottom-up polycentric governance framework for multiscale transformative adaptation and targeted climate investments. WP4 has three components: A). Setting up a polycentric governance model and a “leave no one behind” indicator framework, and developing B). a climate smart governance dashboard to empower farmers, communities, and policy planners to plan and implement bottom-up integrated climate and water risk management interventions, and C) AWARE platform for early warning, early action, and early finance to promote integrated multiscale institutional responses to climate shocks. The Initiative Prospective Agricole et Rurale (IPAR) is supporting the International Water Management Institute (IWMI) in implementing component A of ClimBeR. This report outlines the steps undertaken in mapping adaptation interventions in Senegal as part of ClimBeR activities towards developing a bottom-up polycentric governance model for transformative multi-scale adaptation and timely targeted climate investments. The mapping exercise the review of published grey and peer-reviewed literature and interviews with key stakeholders in national structures involved in food security, climate change and/or governance of early warning systems. The IPAR team mapped 31 adaptation interventions and identified the stakeholders involved in the planning and implementation of the interventions, the geographic focus of the interventions and intended/target beneficiaries of the interviews. All the mapped intervention focused on food security with households and smallholder farmers as primary target beneficiaries. Different institutions, including government agencies and ministries, and development partners and non-govermental organisations are involved in planning and implementation of climate change adaptation in Senegal. The mapping activities, however, revealed that although the institutions identified through this mapping exercise share similar project goals and are involved in similar projects, they use different operational and institutional frameworks resulting in the lack of harmonization of tools deployed in assessing the orientation of the various interventions and duplication of interventions. The lack quality climate data was also identified as a barrier to decision making and governance of adaptation planning and implementation. Ensuring that all stakeholders across all administrative levels and sectors have the same level of information to guide their action is critical in coordinating efforts in enhancing climate adaptation action. Furthermore, a robust governance mechanism to support the governance of adaptation interventions in Senegal remain urgent priorities. Deepening these governance structures that enables cross-sectoral and multi-stakeholder collaboration is critical in enhancing progress in adaptation planning and implementation in Senegal. Mainstreaming of climate change adaptation into national, sectoral and local level policies and budgeting are important enablers of in the governance of climate adaptation.